Strategy for Building an Elderly School Education Brand Using the Hexahelix Model (Implementation of the Program to Prepare Resilient Elderly People at the Fatmawati Elderly School in South Jakarta) - Hasmana, Uci; Tomasowa, Gloria Angelita (The Eastasouth Journal of Social Science and Humanities, 2025)
This study aims to analyze the strategy for developing the educational brand of the Fatmawati Elderly School in South Jakarta through the Hexa Helix Model approach, which is integrated with persuasive communication and Word of Mouth (WOM). This model emphasizes collaboration between six key actors, namely the government, academics, the business world, the community, the media, and the elderly, in creating social innovation in the field of non-formal education. A descriptive qualitative approach was used to understand how the synergy between these actors contributes to strengthening the image of the Elderly School as an inclusive, participatory, and sustainable educational institution. The results show that persuasive communication plays an important role in instilling the values of independence, health, and happiness in the elderly, while WOM is an effective means of spreading information naturally through the positive experiences of participants. The integration of the two within the Hexa Helix framework has succeeded in forming a social communication ecosystem that encourages community participation and strengthens the reputation of the Fatmawati Elderly School as a model for empowering the elderly towards an active ageing society.